A preliminary study on assessing recreation resource impacts at GeoBudaya Berkeley Trail at Lenggong Geopark, Perak, Malaysia / Siti Noorbaizura Bookhari ... [et al.]. - Bookhari, Siti Noorbaizura; Jamaludin, Mas Aiyu; Mat Tahir, Siti Zubaidah; Ishak Hizam, Nor Hidayah; Mohd. Sa’ad, Sri Rahayu; Md. Khalid, Mazzueen; Daim, Mohd Salleh; Hashim, Zakaria (2024)
Recreation ecology is a field of study that assesses, examines and monitors any impact due to visitors coming to carry out recreational activities, especially in natural areas. In line with the recognition of Lenggong Geopark as a National Geopark on 16 September 2021, it is sure to be the primary destination focus for visitors who want to enjoy the uniqueness of geological heritage in this geotourism area. In fulfilling the visitor’s desire to engage more closely with these ecological heritage resources, the trail is a specific medium that connects the resources and the prospective visitors who are interested. However, the large number of visitors can cause problems with the overall quality of the trail system, causing undesirable changes and damaging components of natural resources such as soil, vegetation, wildlife, and water. This problem has directly affected the integrity of the management in maintaining recreational benefits, even creating conflicts between visitors and difficulties in achieving management sustainability. Therefore, this study aims to assess the conditions along the Berkeley GeoBudaya Trail and subsequently provide the management with an understanding of the current status of the trails so that appropriate actions can be taken to curb damage from continuing to occur. Through data collection, 24 sampling points were obtained with a consistent distance gap of 50 meters, each from one to another, making the entire distance of the Berkeley GeoBudaya Trail 1.2 kilometers long. The assessment was carried out using three main techniques, Rapid Survey Technique, Census Sampling Technique, and Cross-sectional Measurements, to determine the factors influencing the recreation resource impact of the trail. The findings of the study show that the current status of recreation resource impacts on the Berkeley GeoBudaya Trail is between low to moderate, preserved, and the environment still retains its naturalness. The significant contribution of such an assessment is believed to be advantageous to the management in ensuring the sustainability of the trail system by accommodating visitation while enhancing the protection of natural resources along the Berkeley GeoBudaya Trail.